MUTU PELAYANAN KESEHATAN TERHADAP KEPUASAN PASIEN DI POLI UMUM PUSKESMAS SIAK HULU II KABUPATEN KAMPAR, 2017 - Widodo, Muhammad Dedi; Renaldi, Reno (Fakultas Kedokteran dan Ilmu Kesehatan Universitas Abdurrab, 2018)
ABSTRACT   Patient satisfaction is a feeling level patients, who arise as a result of the healthcare performance it gained after the patient compares it to what he expects. Based on the beginning survey according to the patient Service in Polyclinic of  Siak Hulu  II Public health center is quite good But not satisfied overall, Lack of facilities and infrastructure and speed in providing services. The purpose of this study is to Analyze the quality of service to patient satisfaction Associated with tangible, Reliability and Responsiveness. This research is a descriptive qualitative research, which aims to obtain information by interview and field observation method where this research was conducted at general polyclinic Public health center Siak Hulu II Kampar Regency in May - June 2017. The  subjects of this study were 6 informants 1 including head of community health clinic and 5 patients of  Polyclinic. Variables in this research are tangible, reliability and responsiveness. The results showed  from 3 variables 2 of them Still not in accordance with the wishes of the patient, Seen from the physical evidence, is still lack of  facilities and infrastructure such as waiting chairs, reading corner and health equipment, In view of the absence of the place so the patient must wait for the examination. Community health clinic should provide sanctions to health workers who are not disciplined And complete the facilities and infrastructure that are still lacking in Polyclinic Public health center Siak Hulu II.